Analysis and Prediction of Green GRDP in Indonesia with Ecosystem Service Value Approach - Gata, Ibnu; Pasaribu, Ernawati (Politeknik Statistika STIS, 2025)
Gross Regional Domestic Product (GRDP) as a measure of economic output in each region has not reflected sustainability because it overlooks the environmental impacts caused. Green GRDP is an important innovation that integrates environmental aspects into sustainable development. Indonesia has committed through TAP MPR IX/2001, Indonesia Emas 2045, and the SDGs to implement sustainable development. This study analyzes and projects Indonesia’s Green GRDP using the Ecosystem Service Value (ESV) approach. Satellite imagery data from MODIS MCD12Q1 and the Cellular Automata–Artificial Neural Network (CA-ANN) method are employed to predict land cover changes, while time series models are applied to forecast GRDP. Variations in provincial ESV are strongly influenced by land cover composition. In 2001, Papua recorded the highest Green GRDP and ESV contribution, whereas by 2020 (projected to 2030), Jakarta leads in Green GRDP but exhibits the lowest ESV contribution percentage. Throughout the period 2001–2030, Papua consistently maintains the highest ESV proportion relative to its Green GRDP. The findings highlight the importance of incorporating ecosystem service values into regional and national economic planning to ensure that economic growth inherently reflects environmental sustainability. This effort should be supported by spatially differentiated development strategies aligned with each region’s ecological capacity.